Tradisi Mangaji Pusaro Pada Masyarakat Nagari Lurah Ampalu di Kecamatan VII Koto Sungai Sarik Sumatra Barat (Studi Living Al-Qur`an) - Illahi, Rahmat Ridho; Fitri, Aulia; Syamsurizal, Syamsurizal; Andika, Erwin Saputra (Al-Kauniyah, 2025)
This study examines the phenomenon of Living Qur’an as manifested in the tradition of mangaji pusaro among the community of Nagari Lurah Ampalu, Padang Pariaman Regency. The research aims to explore the historical background, procedural stages, and the spiritual and social values embedded within this tradition. Employing a descriptive qualitative method with an anthropological approach, data were collected through observation, in-depth interviews, and documentation. The findings reveal that mangaji pusaro is not merely a communal grave-visiting ritual, but a collective spiritual expression that integrates Qur’anic recitation with the local cultural wisdom of Minangkabau. This tradition strengthens social solidarity, cultivates awareness of mortality (dzikrul maut), and serves as a medium for internalizing Qur’anic values in daily life. Thus, mangaji pusaro represents a harmonious synthesis between Islamic teachings and local tradition, contributing to the preservation of religious and socio-cultural values within the Minangkabau community.